The donation-transplantation process and corneal graft failure: A case-control study. - Giovanna Karinny Pereira Cruz; Marcos Antonio Ferreira Júnior; Viviane Euzébia Pereira Santos; Allyne Fortes Vitor; Oleci Pereira Frota; Elen Ferraz Teston; Felipe Machado Mota; Maria Eduarda Gonçalves Zulin; Gustavo Moura Maidana; Letícia Lima Meza; Bruna Dias Abes; Mayra Dias (PLoS ONE)
Introduction The survival after a corneal transplantation depends on several factors, many of which are not fully known. Objective The present study aimed to verify the relationship between the factors inherent to the donation-transplantation process in graft failure. Materials and methods Longitudinal case-control study carried out in a reference service in corneal transplantation in northeastern Brazil, which included transplanted patients with corneal graft failure and their respective controls. The sample consisted of 27 cases of graft failure and 54 controls. Results A total of 427 transplantations were performed between 2010 and 2016 in the studied service, during which 27 cases of corneal graft failure were identified, representing a failure rate of 9.04%. The intergroup descriptive analysis identified the predominance of corneal graft failure in females (cases: 59.26%; control: 55.56%), brown (cases: 65.38%; controls: 53.70%), single (cases: 71.43%; controls: 68.52%) and residents in the capital and metropolitan region (cases: 66.67%; controls: 50%). The mean age of the patients who underwent corneal transplantation was 52.31 years (cases: 56.15 years; control: 50.39 years). Regarding the "type of keratoplasty", the prevalence of penetrating keratoplasty was observed in 87.65% of the transplantations (cases: 81.48%; controls: 18.52%). In addition, 85.19% of the failures were late and 46.91% of the patients subjected to transplantation had already undergone an ophthalmological surgical procedure previously. Conclusion The present study identified the following variables as factors of the donation-transplantation process associated with corneal graft failure: donor button size ≤ 8.25 mm, donor-recipient button size difference less than 0.25 mm, death due to respiratory failure, time interval between enucleation-preservation and corneal endothelial disorder.